The management of human resources in the Asia Pacific: Into the 21st century - Chris Rowley; Malcolm Warner (Management Revue, 2007)
In this introduction, we look at the management of human resources in the Asia Pacific region. We start with an overview of the countries involved, ranging from the hugely populated China to the city-State of Singapore, proposing three categories of economies and the people-management systems, namely the 'developed', the 'developing' and the 'transitional'. After this, we examine the labour markets and employment trends to be found in the region, raising a number of issues relating to future job prospects. We argue that these labour market/employment phenomena and peoplemanagement developments are closely intertwined. A further section sums up the findings of the contributors to this Special Issue. Finally, we present our conclusions.
Keywords: 650; Asia; employment; globalization; Human Resource Management (HRM); Industrial Relations (IR); Multinational Corporations (MNCs); Beschäftigung; Globalisierung; Personalmanagement; Arbeitsbeziehungen; Multinationales Unternehmen; Asien